Taṭwīr Mahārah al-Ittiṣāl al-Syafahi Lada Muta’allimī al-Lugah al-‘Arabiyyah Lugah Ṡāniyah fī Ta’līm al-Qāim ‘ala al-Nawātij - Rizka Rivensky; Nadwah Daud; Nik Hanan Mustapha (Arabic Education Program IAIN Pekalongan, 2022)
Outcome-based education (OBE) clearly puts the ‘learning outcomes’ that match the needs of profession atmosphere over the ages. Meanwhile, oral communication is one of the language skills that have been of interest to most professional fields out there. The International Islamic University Malaysia has been enduring OBE for years. An educational system is one of the predisposing and exciting elements for developing skills nonetheless language skills to some extent, as it may prepare the learners to practicing and developing language skills among themselves. Hence, the study aims to cover the educational activities useful for the learner in the outcome-based education to develop communication skill. It seeks to find out how useful the activities are to develop the learner's communication skill. The researchers relied on the descriptive survey method in conducting the study. The researchers conducted this study on 234 learners, by using a set of aquestionnaire adopted from past studies to look into learners’ views towards development of oral communication skill among them through certain learning activities while they endured OBE. The study concluded that all these activities benefited the learners in developing the skill in many aspects that were clarified in the study result.